Sibling Death after Being Thrown from Window by Brother with Autism: Defenestration, an Emerging High-Risk Behavior. (3rd August 2015) - Sabuncuoglu, Osman; Irmak, Mustafa Yasin; Ucok Demir, Nagehan; Murat, Duygu; Tumba, Can; Yilmaz, Yuksel
Abstract : Children diagnosed with autistic spectrum disorders (ASD) may have serious behavioral problems such as aggression, self-injury, and violence. However, the literature on ASD either overrules any correlation between aggression and ASD or maintains the fact that the efforts to link them have so far been inconclusive. Although severe forms of violence are extremely rare in children with autism, there are a few cases reported in the literature with significant harm to siblings. We hereby report an 8-year-old boy with ASD who caused the death of his sibling by throwing her out of the window. Shared similarities of all defenestration cases indicate a pattern of high-risk behavior threatening the survival of minors. We recommend precautions against this high-risk behavior in children with ASD.